Formação docente continuada no projeto “Trajetórias Criativas” de uma escola no município de Alvorada, RS - Silva, Kátia Oliveira (2018)
This dissertation investigates the continuing formation of five teachers who are part of an educational action called "Creative Trajectories (TC)" at a public school in the city of Alvorada, Metropolitan Region of Porto Alegre / RS. Educational action that is based on the development of authorship, of creation, autonomy and protagonism of young people aged 15 to 17 who did not complete Primary School. The investigative question consisted in know is, how happens the continuous formation of the teachers of the Creative Trajectory Project. It was a qualitative study based on the Participant Research, which used participant observation with information in the field diary, conversation wheels (in the B.S. School and in the UFRGS) in the collection of information, questionnaires, interviews and reading and document analysis. According to the production of the information and, in a special way, the transcription of the subjects' speeches, I made the intersection of these with the theories and the discussion proposal. The conclusive analysis of the dissertation was that the continuous training of the professionals of the Creative Trajectory Project is basically based on the daily classroom and pedagogic activities, which are directly linked to the context of the students. Teachers also use the space of pedagogical meetings to exchange experiences and promote shared learning among peers. They expand their knowledge through online courses and presential classes of fewer hours and participate in the courses offered by the College of Application (UFRGS) in the socalled immersions. Faced with this situation, it is possible to affirm that continuing teacher education lacks more specific and characteristic themes about the realities of youth, and that these teachers struggle against the precariousness of the world in in teaching struggling to keep up to date. Each of these professionals presented an untiring search for the knowledge necessary to teach, especially with the youth of the TC, becoming, themselves, autonomous authors of their knowledge, protagonists in the pedagogical action of each new day, creators of situations and proposals involving both for them as well as for the students Exactly what the Creative Trajectory Project intends to accomplish with the youth that participate in it.